HEALTH STATUS AND PSYCHO-PHYSIOLOGICAL PROBLEMS OF PUPILS' GOING TO NEW TYPES OF EDUCATIONAL INSTITUTION - A.G. Mutalov; G.P. Shiryaeva; G.A. Vachitova; N.F. Druzhinina ("Paediatrician" Publishers LLC, 2007)
The paper deals with complex assessment of somatic and psychological health of schoolchildren trained in private sector of educational institutions. The results of the programme developed and introduced into the educational process are presented in the paper. This programme entitled medico- psychological and pedagogical adaptation improves psychosocial capacities of schoolchildren.Key words: schoolchild, health, psychosocial adaptation.